2004
DOI: 10.1016/j.femsle.2004.08.034
|View full text |Cite
|
Sign up to set email alerts
|

TheAspergillus nigerannexin,anxC3.1is constitutively expressed and is not essential for protein secretion

Abstract: An annexin, anxC3.1, was isolated and characterised from the industrially important filamentous fungus Aspergillus niger. anxC3.1 is a single copy gene encoding a 506 amino acid predicted protein which contains four annexin repeats. Disruption of the anxC3.1 gene did not lead to any visible changes in phenotype, nor in the levels of secreted protein, nor specifically in glucoamylase production, suggesting no major role in secretion. anxC3.1 expression was found to be unaltered under a variety of conditions suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The sequence analysis of KO cassettes indicated that in both constructs anxC4 ORF was disrupted and the production of a functional protein is unlikely. Previous studies have confirmed the loss of protein function using this disruption approach [7,13]. AnxC4 disruptants did not show any specific phenotype when subjected to various growth conditions.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The sequence analysis of KO cassettes indicated that in both constructs anxC4 ORF was disrupted and the production of a functional protein is unlikely. Previous studies have confirmed the loss of protein function using this disruption approach [7,13]. AnxC4 disruptants did not show any specific phenotype when subjected to various growth conditions.…”
Section: Discussionsupporting
confidence: 52%
“…The preparation of the anxC4 disruption cassette was as described previously [7]. Briefly, the anxC4 gene of A. fumigatus (~2.7 kb, Afu3g07020, Broad institute) was cloned as an approximately 5 kb PCR product containing 5′ and 3′ flanking regions in pGEM-T Easy vector.…”
Section: Construction Of Disruption Cassette and Fungal Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sequence analysis revealed no other annexin in C. neoformans and therefore if another molecular player is responsible for redundancy in annexin functions, it could not be readily identified by sequence homology. Our data is similar to what has been previously shown for Aspergillus spp, where no obvious phenotypes were observed upon deletion of annexin genes (13, 15, 16). Likewise, in Neurospora crassa an annexin deleted strain had no gross growth or filamentation defects (40).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests roles in membrane repair, constitutive or stress‐induced autophagy, stromule formation and exo‐/endo‐cytosis. Secretion from the A. niger anxc3.1 mutant appears normal (Khalaj et al. , 2004a), suggesting that other or no annexins participate in exocytosis.…”
Section: Activities and Possible Functionsmentioning
confidence: 99%